Investigations of Optical Coulomb Blockade Oscillations in Plasmonic Nanoparticle Dimers - Lamessa Gudata; Jule Leta Tesfaye; Abela Saka; R. Shanmugam; L. Priyanka Dwarampudi; Nagaraj Nagaprasad; B. Stalin; Ramaswamy Krishnaraj (International Journal of Photoenergy)
The exploration of Coulomb blockade oscillations in plasmonic nanoparticle dimers is the subject of this study. When two metal nanoparticles are brought together at the end of their journey, tunnelling current prevents an infinite connection dipolar plasmon and an infinite amplification in the electric fields throughout the hot spot in between nanoparticles from occurring. One way to think about single-electron tunnelling through some kind of quantum dot is to think about Coulomb blockage oscillations in conductance. The electron transport between the dot and source is considered. The model of study is the linear conductance skilled at describing the basic physics of electronic states in the quantum dot. The linear conductance through the dot is defined as G=lim⟶0I/V in the limit of infinity of small bias voltage. We discuss the classical and quantum metallic Coulomb blockade oscillations. Numerically, the linear conductance was plotted as a function gate voltage. The Coulomb blockade oscillation occurs as gate voltage varies. In the valleys, the conductance falls exponentially as a function gate voltage. As a result of our study, the conductance is constant at high temperature and does not show oscillation in both positive and negative gate voltages. At low temperature, conductance shows oscillation in both positive and negative gate voltages.